New synonyms of Euconnus (Tetramelus) kraussi Reitter, 1880 (Coleoptera, Staphylinidae, Scydmaeninae) - Hlaváč, Peter; Meybohm, Heinrich (Zootaxa, 2021)
The subgenus Tetramelus Motschulsky, 1869 with its currently 109 palaearctic species, is the largest Palaearctic subgenus of the largest world scydmaenine genus Euconnus Thomson, 1859. The nomenclatural validity of the subgenus-name has been recently supported by a detailed morphological study (Jałoszyński 2015). Euconnus (Tetramelus) kraussi was described by Edmund Reitter (1881a), with the type locality indicated as Caucasus, Martkopi. This was the second species of the subgenus Tetramelus known to occur in the entire Caucasus region, after Euconnus (Tetramelus) reitteri Saulcy, 1878, the latter with unknown type locality. The former was treated as a junior synonym of the latter by Croissandeau (1898), and as a subspecies by Karaman (1973). A modern redescription and illustration of the aedeagus was given by Vít & Hlaváč (1998), together with a key to all species of Tetramelus known at that time from the Caucasus. Castellini (2006: 102) placed Euconnus (Tetramelus) kraussi as a junior synonym of Euconnus (Tetramelus) reitteri. This taxonomic act was based just on the similarity of aedeagi of these two taxa illustrated by Vít & Hlaváč (1998). No type material was studied. Euconnus (Tetramelus) reitteri is smaller, only 1.25-1.30 mm long, against 1.40-1.60 mm for Euconnus (Tetramelus) kraussi. To combine this with differences on the aedeagus and with the allopatric distribution, we regard these two forms as two different species. Later, two new species were described, Euconnus (Tetramelus) marinae Franz, 1979, the type locality „Kachetien nächst Shuamta“ and Euconnus (Tetramelus) nachuzrischwilii Franz, 1986, the type locality „nördlich von Anamuri in etwa 1000 m“. Both were included in the key of Vít & Hlaváč (1998). The type material of both these species was found well-preserved in the Natural History Museum in Vienna (NMW), and thanks to Dr. Harald Schillhammer it was available to the senior author for study. A detailed study of this material proved that both species were conspecific with Euconnus (Tetramelus) kraussi, and their synonymy is formally established here. We are also providing new records for this species, which is so far endemic to eastern Georgia, well delimited by the Meskheti-Likhi range. The material treated in this study is deposited in the following collections: MNHN – Muséum National d‘Histoire Naturelle, Paris, France; NMW – Naturhistorisches Museum Wien, Vienna, Austria; PCAP – private collection of Andreas Pütz, Eisenhüttenstadt, Germany; PCHM – private collection of Heinrich Meybohm, Großhansdorf, Germany; PCMS – private collection of Michael Schülke, Berlin, Germany; PCPH – private collection of Peter Hlaváč, Prague, Czech Republic. The distributional map was created using Encarta software.